2011
DOI: 10.1128/jvi.00078-11
|View full text |Cite
|
Sign up to set email alerts
|

Blocking eIF4E-eIF4G Interaction as a Strategy To Impair Coronavirus Replication

Abstract: Coronaviruses are a family of enveloped single-stranded positive-sense RNA viruses causing respiratory, enteric, and neurologic diseases in mammals and fowl. Human coronaviruses are recognized to cause up to a third of common colds and are suspected to be involved in enteric and neurologic diseases. Coronavirus replication involves the generation of nested subgenomic mRNAs (sgmRNAs) with a common capped 5 leader sequence. The translation of most of the sgmRNAs is thought to be cap dependent and displays a requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
102
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(103 citation statements)
references
References 24 publications
1
102
0
Order By: Relevance
“…Alterations of factors involved in viral transcription and translation may affect viral replication. Coronavirus replication involves the generation of nested subgenomic mRNAs (sgmRNAs) with a common capped 5′ leader sequence [51]. To organize optical transcription of sgmRNAs, its 5′ terminal leader sequences need to interact with intergenic (IG) sequences just upstream of each open reading frame (ORF).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alterations of factors involved in viral transcription and translation may affect viral replication. Coronavirus replication involves the generation of nested subgenomic mRNAs (sgmRNAs) with a common capped 5′ leader sequence [51]. To organize optical transcription of sgmRNAs, its 5′ terminal leader sequences need to interact with intergenic (IG) sequences just upstream of each open reading frame (ORF).…”
Section: Discussionmentioning
confidence: 99%
“…The translation of most of the sgmRNAs requires eukaryotic initiation factor 4F (eIF4F), which is composed of eIF4A, eIF4E, and eIF4G. Regina Cencic et al have reported that replication of human coronavirus 229E was significantly inhibited by blocking the interaction between eIF4E and eIF4G [51]. In the case of vesicular stomatitis virus and influenza virus, viral replication was also inhibited by silencing eIF4G1 [54,55].…”
Section: Discussionmentioning
confidence: 99%
“…In MHV, p38 MAPK activation results in the phosphorylation of eIF4E, which facilitates virus protein synthesis and the subsequent production of infectious virus (Banerjee et al, 2002). Cencic et al reported that targeting the eIF4F complex is a strategy for blocking CoV infection (Cencic et al, 2011). eIF4E is a downstream molecule of p38 MAPK and Fig.…”
Section: The Possible Mechanism By Which P38 Facilitates Viral Replicmentioning
confidence: 99%
“…4EGI‐1 inhibited xenograft melanoma and breast cancer tumor growth with negligible toxicity (Chen et al., ). 4E1RCat is a molecule identified in a screen to bind to eIF4G to hinder eIF4F assembly (Cencic et al., ), and 4E2RCat was identified to prevent eIF4E interaction with eIF4G (Cencic et al., ). Both inhibit cap‐dependent translation and reverse drug resistance in a lymphoma model, but neither molecule has been studied in melanoma.…”
Section: Targeting Protein Synthesis For Melanoma Therapymentioning
confidence: 99%